2013
DOI: 10.4172/2157-2518.s13-003
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Density Regulates Extracellular Proteolysis via Modulation of Cellular Contractility

Abstract: The Extracellular Matrix (ECM) undergoes changes in composition and organization during tumor progression. In breast cancer, increased deposition and cross linking-induced alignment of collagen I create a stiffer microenvironment that directly contributes to cancer invasion. While ECM stiffness-induced invasion has been documented, it remains unclear if ECM density also contributes to invasion independent of ECM stiffness. In this paper, using collagen I-coated glass coverslips of varying density, we sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
(54 reference statements)
0
17
1
Order By: Relevance
“…This implies that it is the tugging force that is responsible for the maturation of invadopodia and not the stiffness of the matrix. Furthermore, other studies performed in 2D cultures have shown that increasing collagen matrix stiffness results in an increase in the number of invadopodia (Alexander et al, 2008;Artym et al, 2015;Das et al, 2013). While our study has found that the number of invadopodia is unaffected by tugging forces, the length is, however, clearly affected.…”
Section: Discussioncontrasting
confidence: 55%
“…This implies that it is the tugging force that is responsible for the maturation of invadopodia and not the stiffness of the matrix. Furthermore, other studies performed in 2D cultures have shown that increasing collagen matrix stiffness results in an increase in the number of invadopodia (Alexander et al, 2008;Artym et al, 2015;Das et al, 2013). While our study has found that the number of invadopodia is unaffected by tugging forces, the length is, however, clearly affected.…”
Section: Discussioncontrasting
confidence: 55%
“…3E,F ). Together, these results suggest that increase in MMP secretion rate leads to increased invasion and ECM degradation 23 .…”
Section: Resultsmentioning
confidence: 67%
“…Whenever a cell comes in contact with ECM fibre(s) it secretes MMPs at the rate of λ per second at the site of ECM fibre(s), where λ represents the intrinsic MMP production rate. This ECM-dependent MMP secretion rule was chosen in line with our observations that increase in ECM density enhances MMP secretion 23 . Similar ECM density-dependent MMP secretion profile was observed when MCF-7 cells were cultured on collagen with varying densities ( Supp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collective invasive cell behaviors and patterns are greatly influenced by the heterogeneity of ECM micro-structures. At the molecular level, the ECM protein concentration and ECM components determine the ECM sub-micron structure and mechanical properties [ 9 14 ]. At the tissue scale, the structural heterogeneity and anisotropy of native tissues are primarily caused by the complex localized ECM microenvironments and their size, density and orientation.…”
Section: Introductionmentioning
confidence: 99%